Prof. Jeffrey Marks: endoscopic surgery is the best way to manage gastrointestinal disease - Zhang, Tracy (Annals of Laparoscopic and Endoscopic Surgery, 2017)
The 15th World Congress of Endoscopic Surgery (WCES 2016) in conjunction with Endoscopic and Laparoscopic Surgeons of Asia (ELSA 2016) and 15th Chinese National Congress of Laparoscopic and Endoscopic Surgery (CSLES 2016) was held successfully from Nov. 9th to Nov. 12th in Suzhou, China.